Service family cost estimation based on case-based reasoning - Tay, Choon Khai (2017)
In recent years, companies and organisations are competing to offer high varieties of customised services to increase revenues and customers’ satisfaction. One of the effective ways to create service variations is to adopt product family design theories and methodologies. Consequently, novel service design concepts such as service family and service platform have been developed. However, research work related to service family costing is found to be scarce. Furthermore, existing service cost estimation methodologies are not feasible for estimating the costs of a service family.